Perceptual training effects on anticipation of direct and deceptive 7-m throws in handball - Alsharji, K. E.; Wade, M. G. (Journal of Sports Sciences, 2016)
We examined the effectiveness of perceptual training on the performance of handball goalkeepers when anticipating the direction of both direct and deceptive 7-m throws. Skilled goalkeepers were assigned equally to three matched-ability groups based on their pre-test performance: a perceptual training group (n = 14) received video-based perceptual training, a placebo training group (n = 14) received video-based regular training and a control group received no training. Participants in the perceptual training group significantly improved their performance compared to both placebo and control groups; however, anticipation of deceptive throws improved less than for direct throws. The results confirm that although anticipating deception in handball is a challenging task for goalkeepers, task-specific perceptual training can minimise its effect and improve performance.